Osteopontin: Relation between Adipose Tissue and Bone Homeostasis - Carolina De Fusco; Antonietta Messina; Vincenzo Monda; Emanuela Viggiano; Fiorenzo Moscatelli; Anna Valenzano; Teresa Esposito; Chieffi Sergio; Giuseppe Cibelli; Marcellino Monda; Giovanni Messina (Stem Cells International)
Osteopontin (OPN) is a multifunctional protein mainly associated with bone metabolism and remodeling. Besides its physiological functions, OPN is implicated in the pathogenesis of a variety of disease states, such as obesity and osteoporosis. Importantly, during the last decades obesity and osteoporosis have become among the main threats to health worldwide. Because OPN is a protein principally expressed in cells with multifaceted effects on bone morphogenesis and remodeling and because it seems to be one of the most overexpressed genes in the adipose tissue of the obese contributing to osteoporosis, this mini review will highlight recent insights about relation between adipose tissue and bone homeostasis.